IMPLEMENTASI UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 6 TAHUN 2014 TENTANG DESA (Studi Pada Fungsi Badan Permusyawaratan Desa Di Desa Bintang Ninggi II Kecamatan Teweh Selatan Kabupaten Barito Utara) - Akhmad Rafi`i; Dr. Kusnida Indarajaya, M.Si; Nurul Hikmah, S.Sos.,M.AP (Universitas Palangka Raya, 2020)
This thesis is intended to describe the function of monitoring the performance of the village Consultative Body Village head rural districts Bintang Ninggi II teweh north south district Barito. The purpose of this study to describe and analyze the problems of lack of traction on the village consultative body to position ourselves. Method in this research uses qualitative research methods by reducing the data. The theory used in this study there was a theory George C. Edward III stating that four variables were instrumental in achieving the successful implementatition, 1. Communication 2. Namely 3. The disposition of resources 4. Bureaucratic structure